Fekete-Szegö Functional for Bi-univalent Functions Related with Gegenbauer Polynomials. (26th April 2022) - Ahmad, Ibrar; Ali Shah, Syed Ghoos; Hussain, Saqib; Darus, Maslina; Ahmad, Babar
Abstract : In this paper, we introduce and investigate a new subclass of bi-univalent functions related with generating function of Gegenbauer polynomials. We will mainly find bounds on Maclaurin series coefficients for functions belonging to this class. We also study the famous Fekete-Szegö type problem for this subclass which is obtained. We will also point out many special cases as corollaries.